ECOLOGICALLY SAFE NON-TRADITIONAL ENERGY FROM RENEWABLE RAW MATERIALS - Криворотько, В. М.; Ісаєнко, В. М. (Proceedings of National Aviation University (archive), 2021)
Prospects for the use of biomass as an environmentally friendly renewable energy source are considered. The possibilities and expediency of using oilseeds and, in particular, rapeseed for the production of non-traditional environmentally friendly motor fuel for diesel engines, its main physical and chemical parameters, environmental and operational characteristics and the potential of vehicles capable of running on this fuel are analyzed.